Thermal conductivity coefficient UO[2] of theoretical density and regular stoichiometry; MATEC Web of Conferences; Vol. 92 : Thermophysical Basis of Energy Technologies (TBET-2016) - Kuzmin A. V. Arian Valerievich (2017, 2017)
Title screen